Retrospective Observational Study of Outcomes in HER2-Positive Metastatic Breast Cancer (mBC) Patients Treated with Ado-Trastuzumab Emtansine (T-DM1) and Subsequent Treatments After T-DM1 in the United States - Neelima Denduluri; Janet L. Espirito; Michelle D. Hackshaw; Chuck Wentworth; Tamy Recchia; Winghan J. Kwong (Adis, Springer Healthcare, 2022)
Abstract Background Limited evidence exists on real-world outcomes with ado-trastuzumab emtansine (T-DM1) treatment and the effectiveness of subsequent therapies. Objective This study evaluated treatment patterns and outcomes of patients treated with T-DM1 and post-T-DM1 therapy in the United States. Patients and methods Adult patients with HER2-positive (HER2+) metastatic breast cancer (mBC) initiating treatment with T-DM1 between 1/1/2013 and 9/30/2018 were included and followed through 12/31/2018. Data were obtained from the iKnowMed electronic health record. Demographic, clinical, and pre- and post-T-DM1 treatment characteristics were described. The Kaplan-Meier method was used to estimate time to treatment discontinuation (TTD) and overall survival (OS). Results Of 318 patients treated with T-DM1, 184 (57.9%) had prior treatment with pertuzumab. The median age was 58 years. Most patients had visceral disease (93.4%), and 62.3% had two or more prior treatments for mBC before T-DM1 (range 0-9). The most common subsequent regimens were trastuzumab + vinorelbine (22.5%), HER2-targeted monotherapy (22.5%), and trastuzumab + other chemotherapy (19.6%). Median TTD with T-DM1 was 5.9 months (95% confidence interval [CI] 4.6-6.9); median OS from the start of T-DM1 therapy was 19.2 months (95% CI 16.8-24.5). Conclusions Patients treated with T-DM1 in this study appeared to have more advanced disease than patients in clinical trials and were treated in later lines of therapy. Variability was observed across subsequent therapy selections. Treatment patterns and outcomes appeared comparable for patients who received prior pertuzumab. The short treatment durations and survival with T-DM1 therapy in the real-world setting underscore the need for effective post-trastuzumab therapies.